Reforms in education and training to meet Malaysia's human resource needs in the 21st century / Ramna Veni Petchimuthu - Ramna Veni, Petchimuthu (2004)
The main purpose of this study is to emphasise on the education and training to fulfil the Human Resource requirement of quality and skilled manpower. The future growth of the economy will place greater demand for a high quality labour force which is versatile and adapts quickly to a changing industrial environment. In order to ensure that the skills of our workforce are relevant, there has to be regular and close monitoring the curricula of the educational and training institutions to meet the demand for news skills arising from rapid technological developments. The 21st century brings a new paradigm, a shift to knowledge-based economy, which is a part of a wider plan to achieve fully developed country status by 2020. In support of the knowledge-based economy and to enhance productivity and competitiveness, the principle trust of Human Resource Development will be the creation of a strong human resource base. Therefore an efficient and responsive education and training system need to be developed to meet the demand for a knowledgeable and highly skilled labour force that is equipped with positive values and attitudes.